2012
DOI: 10.1149/2.003201ssl
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Activation and Crystallization by Low-Temperature Microwave Annealing for Improved Quality of Amorphous Silicon Thin-Film Transistors

Abstract: In this study, activation and crystallization in short channel amorphous Si TFTs were demonstrated using a novel microwave annealing (MWA) technique. Both low-temperature MWA and rapid thermal annealing (RTA) were compared to study the dopant activation level. We successfully activated the source/drain region, improved the electronic mobility and suppressed the short-channel effects using low temperature MWA. This can reduce the annealing temperature and processing time below that of solid phase crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Three distinctive (1 1 1), (2 2 0) and (3 1 1) Bragg peaks are commonly observed in thermally [19] and microwave [1] annealed amorphous silicon with the preferred (1 1 1) orientation [1,19] as in figure 1. The integrated intensities (in arbitrary units) of (1 1 1) peak after the annealing at 600 and 700 °C were 438 and 610, respectively, indicating better crystallinity [20] for the film annealed at higher temper ature.…”
Section: Structural Characteristics Of Amorphous and Crystallized Filmsmentioning
confidence: 95%
See 2 more Smart Citations
“…Three distinctive (1 1 1), (2 2 0) and (3 1 1) Bragg peaks are commonly observed in thermally [19] and microwave [1] annealed amorphous silicon with the preferred (1 1 1) orientation [1,19] as in figure 1. The integrated intensities (in arbitrary units) of (1 1 1) peak after the annealing at 600 and 700 °C were 438 and 610, respectively, indicating better crystallinity [20] for the film annealed at higher temper ature.…”
Section: Structural Characteristics Of Amorphous and Crystallized Filmsmentioning
confidence: 95%
“…Amorphous silicon (aSi) films are widely used in thin film transistors (TFTs) for large displays [1]. They are suitable for optical devices, such as optical sensing [2], x-ray imaging [3], both based on TFTs, and wave guides [4], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects are ascribed to the details of microwave absorption, which selectively affects Si-H bonds, and thus hydrogen bonds were restructured [31]. Some studies have reported microwave annealing in the thin-film coating technology [32][33][34][35]. The MWA has two major microwave heating processes: ohmic conduction and dielectric polarization losses, mainly influenced by the thickness and conductivity of the thin films; and the other is the dielectric permittivity of the thin film materials [36].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the portion of Al‐O bonding states in the films fabricated by microwave annealing was very similar to that in the films fabricated by thermal annealing at 400 °C, supporting the contention that high‐quality Al 2 O 3 /BN composite films can be achieved by microwave annealing at room temperature. Whereas thermal annealing provides thermally activated energy by heating conduction for a longer time during the sol‐gel process, microwave annealing supplies electronically excited energy by microwave absorption for a shorter time …”
Section: Introductionmentioning
confidence: 99%